Breast Rash After Breast Reduction: A Case Study. Issue 2 (April 2016) - Evans, Alison E.; Ridgway, Emily B.
Abstract : Breast reduction surgery is one of the most common procedures done by plastic surgeons. Although not detrimental to the final outcome, allergic reaction can negatively impact the postoperative course. This case presentation paints the classic picture of allergic reaction after breast surgery, likely due to skin glue. The typical signs of intense pruritus and erythematous rash surrounding incisions bilaterally are present. The patient was treated with our institutional protocol with good results. Our protocol is presented and further questions posed.